Perioperative management of acute kidney injury after microwave ablation of hepatic hemangioma - Bin Hu; Hong-Bo Huan; Yu-Liang Tu; Jun Gao; Chang-Le Wu; Wei Zhao; Li-Yuan Sun; Xin Jin; Zi-Man Zhu; Da-Dong Wang; Kai Jiang (BMC Cancer)
Abstract Objective To improve treatment options for acute kidney injury (AKI) after microwave ablation (MWA) of hepatic hemangioma (HH). Methods From January 1, 2021, to October 28, 2024, 117 patients with HH were treated by MWA at our center, and 2 of them occurred AKI after operation. The preoperative and postoperative data of 2 patients were retrospectively analyzed. Results During the MWA for patients with HH, hemoglobinuria may occur during and after surgery, which may even lead to AKI. A sequential treatment consisting of sodium bicarbonate alkalization, rapid fluid replacement, diuresis and dialysis treatment were given to the patient as early and timely. And their renal function returned to normal. Conclusion Patients with AKI after MWA of HH can fully recover. It suggested that MWA is an effective and safe treatment for HH patients.